To be Manobo (Manila Travel Time in cooperation with the National Commission for Culture and the Arts,.. et al., 1996)
Features the Manobo, an indigenous group in Agusan del Sur, through their rituals, song and dance.
VHS format.
Susan Calo Medina, host / producer ; Floy Quintos, scriptwriter.
Keywords: Manobo -- Social life and customs; Manobo -- Marriage rites and ceremonies; Agusan del Sur -- Description and Travel